Diagnosis and surgical management of isolated inferior oblique palsy - Wu, Xiao-Fei (International journal of ophthalmology, 2020)
To describe the etiology, clinical characteristics, surgical options and surgical outcomes of isolated inferior oblique palsy (IOP). A retrospective review was performed on patients with isolated IOP who were seen between January 2010 and June 2017. The following clinical data were obtained from the patients' charts: visual acuity, ocular alignment, ocular motility, cyclotorsion, stereoacuity, Parks three-step test, surgical methods, surgical outcomes and complications. Surgical success was defined as horizontal deviation ≤10 prism diopters (PD) and a vertical deviation ≤5 PD in primary gaze at both near and distant vision as assessed at last follow-up. The records from a total of 18 patients (8 males and 10 females) with an average age of 27.56y were included in this study. The right eye was affected in 11 patients, the left in 6 patients and both eyes in 1 patient. Twelve cases (66.7%) were congenital and 6 (33.3%) were acquired IOP. The 6 acquired cases involved 2 resulting from orbital trauma/surgery, 2 from midbrain microvascular ischemia, 1 from myasthenia gravis and 1 of unknown etiology. Strabismus surgery was performed in 13 cases. Surgical techniques included weakening of superior oblique and vertical rectus recession and resection. After a mean follow-up of 15.11mo, the corrected vertical deviation in primary position was 19.92±8.52 PD ( =0.000) and the corrected horizontal deviation was 14.31±12.68 PD ( =0.002). The surgical success rate was 61.5% and no surgical complications were present. Isolated IOP represents a rare condition, with most cases (66.7%) involving a congenital basis. The acquired cases included vascular, orbital trauma/surgery and myasthenia gravis. Weakening of the ipsilateral superior oblique muscle and/or contralateral superior rectus recession often resulted in favorable surgical outcomes with a surgical success rate of 61.5%.